Rickettsial diseases in Brazil and Portugal: occurrence, distribution and diagnosis - Galvão, Márcio Antonio Moreira; Silva, Luiz Jacintho da; Nascimento, Elvira Maria Mendes; Calic, Simone Berger; Sousa, Rita de; Bacellar, Fátima (Revista de Saúde Pública, 2005)
The present study is an update review on the occurrence and diagnosis of rickettsial diseases in Brazil and Portugal, aiming at promoting their epidemiological surveillance in both countries. A literature review was carried out and unpublished data of laboratories and surveillance systems were presented. The results described the occurrence of rickettsial diseases and infections in Brazil and Portugal, including other new and still poorly understood rickettsial infections. Current diagnostic methods were discussed. As in many other countries, rickettsial diseases and infections seem to be an emerging public health problem. Treated as a minor problem for many decades, the interest in these infections has increased in both countries but further studies are needed to establish their role as a public health problem.